Basic Methodical Grounds of Teaching International Students Chinese Field-specific Terms in Technical Institutes of Higher Education (in the Context of Polymer Production); Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Khorechko U. V. Uliana Viktorovna; Scherbinin A. I. Aleksey; Lebedeva I. O. Irina Olegovna; Li Bao Gui; Sentsov A. E. Arkady Eduardovich (2015, 2015)
Title screen